The overview of nutritional status, physical activity, menstrual patterns, and aashing behavior on teenagers - Bahar, Hartati; Lestari, Hariati; Hasanah, Indah Nur (Universitas Islam Negeri Alauddin Makassar, 2024)
Anemia is a common health problem in Indonesia. One-third of teenagers, or three to four out of ten teenagers, suffer from anemia. The aim of this research was to determine the nutritional health picture of adolescent girls at SMPN 12 Kendari based on their level of exercise, menstrual cycle, and habit of washing their hands with soap (CTPS). The population in this study was 42 grade 9 students. The sampling technique was simple random sampling with a research sample of 30 young women. Questionnaires are used to collect data to measure respondents' attitudes and behavior. The results showed that of the 30 respondents whose data were taken, there were 15 respondents who had a thin nutritional status (50%), there were 20 respondents who did light exercise (66.7%), there were 24 respondents with normal menstrual patterns (80%), and There were 21 respondents who had hand washing behavior that met the requirements (65.6%). It is hoped that young women will pay more attention to their daily consumption patterns so that they comply with balanced nutrition to improve their nutritional status.